If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1.5y + x + 6y = 4 Reorder the terms: 1 + x + -1.5y + 6y = 4 Combine like terms: -1.5y + 6y = 4.5y 1 + x + 4.5y = 4 Solving 1 + x + 4.5y = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + x + -1 + 4.5y = 4 + -1 Reorder the terms: 1 + -1 + x + 4.5y = 4 + -1 Combine like terms: 1 + -1 = 0 0 + x + 4.5y = 4 + -1 x + 4.5y = 4 + -1 Combine like terms: 4 + -1 = 3 x + 4.5y = 3 Add '-4.5y' to each side of the equation. x + 4.5y + -4.5y = 3 + -4.5y Combine like terms: 4.5y + -4.5y = 0.0 x + 0.0 = 3 + -4.5y x = 3 + -4.5y Simplifying x = 3 + -4.5y
| 5/1.969 | | 0=4x^2-25x+48 | | h(t)=-16t^2+50t+60 | | v=2.5*1.5 | | x+.08x=243 | | 4p+10=-25-3p | | 32=-8v+6(v+6) | | 14x^2-28x+35=0 | | (6/8)/3 | | 26=4(w+3)-2w | | 3+2(x+6)=5(x-1) | | 1x+6y=27 | | 5x(x+12)=90 | | 5(a+30)=100 | | 3/2x-2=7 | | x+(2x-250)=2850 | | 1x+6y=-2 | | 5a+30=155 | | 8.35/.55 | | a^4=1024 | | 2/3(6n-9)=20 | | 36x-9y-3y-4z=18 | | 2v-5=3v+1 | | -16x^2+16*x+65=0 | | 8.35/0.55 | | -2(-4x+5)=-6(-5x-4) | | 5a+2a=11-2-a | | -16x^2-14*x+65=0 | | 4z+27=30+2y | | 9-3x=54 | | 2(11*3)+(10+10)(9+[2*5])= | | 11-3x=3x+37 |